2014
DOI: 10.18052/www.scipress.com/ilcpa.30.89
|View full text |Cite
|
Sign up to set email alerts
|

Galilei was Wrong: Angular Nonradial Effects of Radial Gravity Depend on Density of Matter

Abstract: Although in mathematical sense the actual meaning of Galilei's experiments conducted at leaning tower of Pisa is that he failed to detect any measurable impact of composition of matter on gravitating bodies, the obvious failure is mistakenly interpreted as experimental confirmation of lack of the impact instead. Galilei did not really perform internal validity checks of his experiments, because he did not ensure that he actually measured what he was supposed to measure. However, a modern experiment devised to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Despite mounting experimental evidence that Newton was right [2], [3], mainstream scientists ignored it and left some childishly simple experiments unexplained and unreconciled [2]. Instead of taking seriously the very first definition that Newton has offered in his Principia, physicists and mathematicians "rationalized" his insight and in doing so created few nonsenses and even fake theorem [4].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite mounting experimental evidence that Newton was right [2], [3], mainstream scientists ignored it and left some childishly simple experiments unexplained and unreconciled [2]. Instead of taking seriously the very first definition that Newton has offered in his Principia, physicists and mathematicians "rationalized" his insight and in doing so created few nonsenses and even fake theorem [4].…”
Section: Introductionmentioning
confidence: 99%
“…The new nonradial effects showed that density of matter does matter indeed for nonradial gravitational interactions and that they give rise to clearly repulsive nonradial gravitational interactions as well [5], [2], [3], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations